PENGARUH SOSIALISASI GENDER TERHADAP PEMBENTUKAN POLA PIKIR PEREMPUAN ACEH (Studi Kasus di Banda Aceh dan Aceh Besar) - Miskahuddin, Miskahuddin (UIN Ar-Raniry, 2014)
Discourse on gender is not depleted as discussed and studiedÃ‚Â scientifically until now. Debate in academic circles about gender areÃ‚Â already accustomed discussed and no longer be something foreign.Ã‚Â Even today there are efforts to encourage all of the activities andÃ‚Â programs should be concerned with aspects of gender equality.Ã‚Â Development of previously unknown information about only theÃ‚Â consumption of the current academic has penetrated up to the villageÃ‚Â level, and unknown to many people , both lay and the learnedÃ‚Â knowledge. This occurs because of the reality of gender socializationÃ‚Â undertaken by various parties, including government agencies throughÃ‚Â the empowerment of women and children , as well as by non-governmental organizations ( local and international NGOs ) . ManyÃ‚Â people received information about the gender , clearly establish its ownÃ‚Â thinking paradigm for women in Aceh . To see about women thinkingÃ‚Â about gender Aceh after getting the socialization of NGOs , theÃ‚Â research was conducted.Keywords : Influence , Socialization , Gender